PLGA nanoparticles for heart targeted drug delivery and regeneration of ischemic tissue - Costa, Catarina Alexa de Vilhena e Pamplona (2023)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2023, Universidade de Lisboa, Faculdade de Farmácia.